PEMBAGIAN KERJA SECARA SEKSUAL DAN PERAN GENDER DALAM BUKU PELAJARAN SD - Christiani, Lintang Citra (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract:This study aims to explain the sexual division of labour dan gender roles dominant in textbooks. Mass media tend to reflect critically on dominant ideology that sustain gender inequality. Muted Group Theory and Socialist Feminist Perspective are used to explain a social phenomenon. The finding of this study shows that women are still experiencing oppression sistematically through the sexual division of labour in the textbooks. Text subordinate to reinforce stereotypes of feminine women to be appropriate to work under the domestic domain, while men in the public domain. Curriculum books in 1982 and 1994 gave rise to the traditional gender roles, while the dominant gender roles in 2004 and 2006 are transition gender roles.